THE EFFECT OF USING PADLET ON ELEVENTH-GRADE STUDENTS' PERSONAL LETTER WRITING SKILLS - Selvia, Deby; Latif, Amirudin; Faliyanti, Eva; Siagiyanto, Bambang Eko (Universitas Muhammadiyah Metro, 2025)
This research was conducted in response to the ongoing challenges faced by students in learning English writing skills in non-English-speaking countries, particularly in making writing engaging and effective. The study focuses on the use of Padlet as a digital tool to improve students' personal letter-writing skills. The purpose of this research is to determine whether Padlet significantly improves students' writing scores and affects their overall writing abilities. A quasi-experimental design with a pre-test and post-test control group was employed. The participants were grade XI students of SMA Muhammadiyah 1 Pekalongan, divided into an experimental class using Padlet and a control class using the conventional method. The research used writing tests as the main instrument, assessed through five aspects: content, organization, vocabulary, grammar, and mechanics. Data were collected through pre-tests and post-tests, then analyzed using t-tests to determine statistical significance. The findings show that students taught using Padlet scored higher in all aspects of writing, indicating a significant improvement and positive effect on their writing skills. It can be concluded that Padlet is an effective medium for enhancing writing quality and student engagement. This research suggests that teachers should consider integrating interactive digital tools, such as Padlet, into writing instruction to overcome challenges and boost students' motivation and performance.